Examination of Carpal Canal by Ultrasound in Dogs (Journal of Hama University, 2020)
The aim of this study was to determine the course of the median nerve and its adjacent structures in the carpal canal of 8 healthy dogs by using high-frequency transducers.  Before performing ultrasonography, the transverse and posteroanterior diameters as well as the perimeter of the carpus were measured at just proximal to the side of the carpal pad. The anatomical structures were then determined at two levels of the carpal canal, which were named the proximal and distal levels, on the transverse sonograms.  The cross-sectional areas, perimeters and the transverse and posteroanterior diameters of the median nerve were measured at these levels. Although all the measurements were larger at the proximal level, significant differences between the proximal and distal levels were determined for the cross-sectional area, the perimeter and the transverse diameter of the median nerve. On the transverse sonogram, the deep digital flexor tendon was seen in almost the center of the carpal canal like a comma shape and also it had a small concavity on the caudal side. The superficial digital flexor tendon was seen as an ovoid shape on the transverse sonograms and it was located nearly at the posterior side of the carpal canal. Both tendons were seen as intermediategrade echogenic structures. The median artery was located inside of the concavity of the deep digital flexor tendon. Also, the median nerve was seen at the posteromedial side of the median artery. As a result of this study, the cross-sectional areas of the median nerve ranged between 1.01-2.68 mm2 at the proximal level and between 0.93-1.91 mm2 at the distal level.